(untitled) (Journal of International Studies, 2023)
Abstract: The study aims to draw valuable lessons for Mongolia from the Republic of Korea’s (ROK) successful experiences in export support. Within this framework, the first section of the study provides an overview of key initiatives in industry and foreign trade development that have been implemented since the 1960s. The second section examines the comprehensive content, formats, and implementation methods of export support programs designed for small and medium-sized enterprises, particularly those in use since 2000. This section covers various aspects of export support, including financial assistance, marketing strategies, and technical services. It also includes illustrative examples. The study’s findings recommend specific case studies and insights from South Korea’s export development journey and currently operational programs, which have the potential to benefit Mongolia’s own export efforts. БНСУ-ын Засгийн газраас үндэсний үйлдвэрлэл, экспортоо дэмжиж буй хэлбэрүүд Хураангуй: Уг судалгаа нь БНСУ-ын экспортыг дэмжих чиглэлд олсон амжилт, туршлагаас Монгол Улсад хэрэг болохуйц зарим жишээг тодруулах зорилго агуулсан. Энэ хүрээнд эхний хэсэгт 1960-аад оноос эхлэн хэрэгжүүлсэн аж үйлдвэрлэл, гадаад худалдааг хөгжүүлэх зарим онцлох бодлого хөтөлбөрүүдийг тоймлон судалсан. Хоёрдугаар хэсэгт 2000 оноос хойш хэрэгжүүлж буй жижиг дунд үйлдвэрлэл эрхлэгчдийн экспортыг дэмжих хөтөлбөрүүдийн ерөнхий агуулга, хэлбэр, хэрэгжүүлэх арга барилыг судалсан. Тухайлбал экспортыг дэмжих санхүү, маркетинг, технологийн үйлчилгээнүүд, тэдгээрийн онцлог, хэрэгжүүлж буй арга барилуудыг зарим жишээтэй оруулсан. Судалгааны үр дүнд тус улсын аж үйлдвэрлэл, экспортыг хөгжүүлсэн туршлага, өнөөгийн байдлаар хэрэгжүүлж буй бодлого хөтөлбөрүүдээс Монгол Улсын экспортыг дэмжих үйл хэрэгт нэмэр болохуйц зарим жишээг гаргасан. Түлхүүр үгс: БНСУ, экспорт, үйлдвэрлэл, жижиг дунд үйлдвэрлэгч, бодлого, хөтөлбөр